Learners’ Problems on Open and Distance Learning Institutions in Arunachal Pradesh (International Journal of Scientific Research in Science and Technology, 2025)
The aim of the present study is to find out the problems of Learners of the Open and Distance Learning Institutions of Arunachal Pradesh. A sample of 400 learners of ODL institutions were taken and survey method was applied. The researcher used self-developed tool to find out the problems of learners ODL institutions of A.P. The researcher used the simple percentage for interpreting the data. The findings shows that Open and Distance Learners found satisfactory regarding to Learning Support Services, Learning Materials, Counselling class and communication. Moreover, a finding also indicates few distance learners are dissatisfied with study centre staff, quality of study materials, expert counsellors and communication facilities. Thus, the study highlights the problems of Open and Distance learners relating to learning support services, learning Materials, counselling class and communication in the Open and Distance Learning institutions of Arunachal Pradesh.